2004
DOI: 10.1212/01.wnl.0000117981.35364.1b
|View full text |Cite
|
Sign up to set email alerts
|

Practice Parameter: Diagnostic assessment of the child with cerebral palsy [RETIRED]

Abstract: Abstract-Objective:The Quality Standards Subcommittee of the American Academy of Neurology and the Practice Committee of the Child Neurology Society develop practice parameters as strategies for patient management based on analysis of evidence. For this parameter the authors reviewed available evidence on the assessment of a child suspected of having cerebral palsy (CP), a nonprogressive disorder of posture or movement due to a lesion of the developing brain. Methods: Relevant literature was reviewed, abstract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
337
0
27

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 523 publications
(373 citation statements)
references
References 73 publications
(69 reference statements)
9
337
0
27
Order By: Relevance
“…The decrease in prevalence of bilateral spastic CP may be explained by improvements in neonatal care, but there is no obvious reason for the increase in unilateral spastic CP. Neuro-imaging studies [10,11]suggest that slightly different patterns of brain abnormalities are observed in unilateral and bilateral spastic CP. Thus, it might be possible that prevention has affected the two subtypes differently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in prevalence of bilateral spastic CP may be explained by improvements in neonatal care, but there is no obvious reason for the increase in unilateral spastic CP. Neuro-imaging studies [10,11]suggest that slightly different patterns of brain abnormalities are observed in unilateral and bilateral spastic CP. Thus, it might be possible that prevention has affected the two subtypes differently.…”
Section: Discussionmentioning
confidence: 99%
“…As the number and severity of impairments increase with increasing gestational age [6,7] and birthweight, [8] the type of brain lesion among term or NBW children tends to exhibit a different pattern to that of preterm or low birthweight births. [9][10][11] Time trends for CP prevalence in NBW children vary across studies. [12,13] Most of them reported stable prevalence rates from the 1970s to the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…4 While studies exist looking at comorbidities in children with CP, few exist looking specifically at children with the SQ subtype. This is of particular relevance given that the recent American Academy of Neurology practice guidelines 5 recommends that all children with CP undergo screening for mental retardation,* ophthalmological and hearing impairments, speech and language disorders, and oral-motor dysfunction.…”
mentioning
confidence: 99%
“…Los niños con mejor CI se agrupan en aquellos con mejor funcionalidad motora o más bien aquellos niños con mejor funcionalidad motora tienen mejor CI. Por otro lado, los niños con PC tetraparética tienen un grado de compromiso intelectual mayor que los niños con hemiplejia (Paneth y Stark, 1983;Murphy et al, 1998;Beckung y Hagberg, 2002;Ashwal, S. et al, 2004). Así se resume que aquellos niños con menor afectación motora presentan a su vez un mayor CI.…”
Section: Introductionunclassified